ECB’S MONETARY MEASURES DURING THE FINANCIAL CRISIS - Magdalena RADULESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
This paper presents the main developments of the eurozone during the crisis period and the measures adopted by ECB in this context. The paper especially aims the countries that were the most affected by the crisis, namely: Greece, Cyprus, Ireland, Portugal, Spain and Italy. The public debt of those countries increased greatly and they faced many pressures on the international financial markets.